The Effect of Academic Stress on the Cognitive Function of Medical Students - Suhartini, Sri Mukti; Setyawati, Rena Fuji Erin; Lestari, Winda; Perwita, Prima Yuri; Gunawan, Bhakti (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
Stress, as a body's response to maintaining the balance of bodily functions, can affect academic performance and is categorized as academic stress. Medical education has special characteristics that distinguish it from other study programs due to the higher challenges in the educational process. This study aimed to determine the effect of academic stress on cognitive function in medical students, which was analyzed through the students' grade point average (GPA). The research was carried out using a quantitative method with a cross-sectional design. The subject was a medical student at Universitas Gunadarma. The number of samples was 130 respondents. A Medical Student Stressor Questionnaire (MSSQ) was administered. The student's GPA was collected. The data was analyzed using the Gamma test. The results were obtained that the majority of respondents experienced high-category stress. The majority of medical students had a GPA between 3 to 4. The analysis results showed that there was a significant correlation between the academic stress of the medical student and the GPA (p=0.030). Academic stress has a positive correlation with the cognitive function of medical students. The research results are expected to be input for educational institutions to make efforts to accompany and support students in overcoming academic stress.